Breeding of Biomphalaria tenagophila in mass scale Criação em larga escala de Biomphalaria tenagophila - Florence Mara Rosa; Daisymara P. Almeida Marques; Engels Maciel; Josiane Maria Couto; Deborah A. Negrão-Corrêa; Horácio M. Santana Teles; João Batista dos Santos; Paulo Marcos Zech Coelho (Universidade de São Paulo (USP), 2013)
An efficient method for breeding Biomphalaria tenagophila (Taim lineage/RS) was developed over a 5-year-period (2005-2010). Special facilities were provided which consisted of four cement tanks (9.4 x 0.6 x 0.22 m), with their bottom covered with a layer of sterilized red earth and calcium carbonate. Standard measures were adopted, as follows: each tank should contain an average of 3000 specimens, and would be provided with a daily ration of 35,000 mg complemented with lettuce. A green-house effect heating system was developed which constituted of movable dark canvas covers, which allowed the temperature to be controlled between 20 - 24 ºC. This system was essential, especially during the coldest months of the year. Approximately 27,000 specimens with a diameter of 12 mm or more were produced during a 14-month-period. The mortality rates of the newly-hatched and adult snails were 77% and 37%, respectively. The follow-up of the development system related to 310 specimens of B. tenagophila demonstrated that 70-day-old snails reached an average of 17.0 ± 0.9 mm diameter. The mortality rates and the development performance of B. tenagophila snails can be considered as highly satisfactory, when compared with other results in literature related to works carried out with different species of the genus Biomphalaria, under controlled laboratory conditions. Foi desenvolvido um método eficiente de criação em larga escala de Biomphalaria tenagophila (linhagem Taim/RS) durante o período de 2005-2010. Foi concebida uma instalação que consiste de quatro tanques de alvenaria (9,4 x 0,6 x 0,22) com fundos recobertos por uma mistura constituída de terra vermelha esterilizada e carbonato de cálcio. Foi padronizado que cada tanque de criação conteria em média 3.000 exemplares e receberia diariamente 35.000 mg de ração e alface como complemento. O desenvolvimento de um sistema de aquecimento por efeito estufa constituído de lonas escuras móveis permitiu controlar a temperatura entre 20 a 24 ºC, sistema essencial principalmente nos ...